The Relationship Between Organizational Commitment, Professional Development, and Job Performance of Educators in Public Universities - Prayudi, Ahmad; Sitompul, Gabirel Amadeus; Anwar, Amelia (PT. BATARI EDU CALYA, 2024)
This study investigates the relationship between organizational commitment, professional development, and job performance among educators in public universities. Using a sample of 250 educators from public universities in West Java, Indonesia, the study employed a quantitative approach, incorporating Pearson correlation and multiple regression analyses to examine the influence of organizational commitment and professional development on job performance. The findings revealed that both organizational commitment and professional development have significant positive effects on job performance. Furthermore, an interaction effect was observed, suggesting that educators who exhibit high levels of organizational commitment and actively participate in professional development activities perform better than those with only one of these factors. These results emphasize the importance of fostering both commitment and professional growth in improving educator performance. The study contributes to the literature on educator effectiveness and offers practical recommendations for enhancing job performance in higher education institutions.